Analisis Inovasi Produk dan Keunggulan Bersaing Terhadap Kinerja Pemasaran Pada Produk Rabbani Store di Surabaya - Nugraha Anggoro Safri; Hery Pudjoprastyono (UNHI Press, 2023)
Rabbani is one of the Indonesian Muslim fashion brands that is a pioneer in hijab and Muslim clothing in Indonesia.The number of brands that have sprung up, making competition in the fashion world even tighter. Therefore, different strategies are needed to achieve a competitive advantage. Many factors determine competitive advantage, one of which is product innovation. This research focuses on the study of product uniqueness and product innovation in detail explained through separate indicators focused on Rabbani Store Products. This research seeks to answer whether companies with unique fashion products and product innovations can have a positive influence on marketing performance through competitive advantage. Data analysis was carried out using the component-based SEM method using PLS (Partial Least Square) as an analytical tool in this study. The results of the research that have stated, product innovation can contribute to Marketing Performance, the more Product Innovation increases, Marketing Performance also increases. Likewise, competitive advantage can contribute to Marketing Performance, the more competitive advantage increases, the more Marketing Performance also increases.